Aplikasi Kader JKN Pada BPJS Kesehatan Cabang Sampit - Syarifah Nurhasanah; Slamet Riyadi (STMIK Budi Darma, 2020)
The purpose of the application is to make it easy for PIC Kader Jkn in this case the Financial Staff in managing the achievements and performance of Jkn Cadres and Making Achievement Reports, Activities and Salary Reports of Jkn Cadres. The application is designed on a Web basis using the Codeigniter framework. The method used is by conducting a trial based on the From Checklist tested by the Finance Staff and the Head of the Finance Sector. The design method starts from the stage of data analysis, system design, program development, testing, implementation, evaluation. The result of the design is the Jkn Cadre Application at BPSJ Kesehatan Sampit Branch as the main theme. The conclusion of this thesis is that the JKN Cadre application can provide information about BPJS participants who have arrears in BPJS premium payments and provide information about the achievements and performance activities of JKN cadres.